Literature Review: Physical Activity In Elementary School Students' Outdoor Educational Learning - Hernawan Hernawan (UNIB Press, 2023)
Outdoor education is an activity outside the school which is an activity outside the classroom. Such as playing in the school environment, parks, camping, and others. However, outdoor education does not just move lessons out of the classroom, but is carried out by inviting students to unite with nature and carry out activities that lead to the realization of changes in students' behavior towards the surrounding environment through the stages of awareness, understanding, responsibility, and behavior. The purpose of this study was to be able to examine the effect of outdoor education on the physical activity of students in elementary schools. The writing of this scientific article uses the literature review research method which originally came from 581 literature sources and then reviewed into 16 literature taken from two databases (Google Scholar and PubMed) which show physical activity and outdoor education. The results showed that every student with high physical activity had a good level of fitness. Students who do a lot of physical activity will get better physical fitness. It can be concluded that both learning activities outside the classroom have a significant positive impact, with learning outside the classroom focusing on academic development and a holistic learning experience, while physical activity focuses on physical health and individual well being.